The Influence of Greek Philosophy to the development of Islamic Thought - Chaerul Mundzir,; Jusmiati, (Tumanurung: Jurnal Sejarah dan Budaya, 2024)
This research aims to, firstly, understand the general description and history of the development of philosophy, secondly understand the period of Greek philosophy, and thirdly understand the influence of Greek philosophy on Islamic thought. The type of research used is Library Research. The results of this research are, first, philosophy is a science that investigates everything that exists in depth by using reason to get to its essence. The history of philosophy began on the coast of the Mediterranean Ocean, Eastern part in the 6th century BC. Since the beginning, philosophy has been characterized by mankind's desire to answer questions about nature, humans and God. Second, the period of Greek philosophy was a very important period in the history of human civilization because at that time there was a change in human thought patterns from mythcentric to logo-centric. And third, the influence of the entry of Greek philosophy into Islamic thought, namely awakening Muslims to study various sciences in depth, and fostering Muslims' desire to study natural sciences and philosophy. Therefore, the birth or emergence of philosophy in the Islamic world cannot be separated from the chain of migration of Greek philosophy into the Islamic world through the translation of Greek works.